2021
DOI: 10.1029/2021gl095248
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Deformation and Detachment in the Sulu Orogenic Belt: New Constraints From Onshore‐Offshore Wide‐Angle Seismic Data

Abstract: The continents on the earth are formed by several ancient continental blocks through millions of years of divergence and convergence. North China (Figure 1a) was mainly formed by the convergence of the Sino-Korean Block (SKB) and the Yangtze Block (YZB) in the Triassic (Wan, 2012). The collision between SKB and YZB formed the famous Qingling-Dabie-Sulu orogenic belt (QDSOB), which has been proven to be the world's largest ultrahigh-pressure metamorphism (UHPM) and high-pressure metamorphism (HPM) belt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…After pre-processing the data, including linear time drift correction, OBS relocation, denoising, and deconvolution (Figure 4), we picked the travel-times of the refraction and reflection seismic phases from all the useful OBSs and land stations (Liu et al, 2015;Liu et al, 2021). We found that most of the OBS stations provided useful data at offsets of up to 100 km (Figure 5), although a few OBS stations only provided effective observations within 60 km offsets.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After pre-processing the data, including linear time drift correction, OBS relocation, denoising, and deconvolution (Figure 4), we picked the travel-times of the refraction and reflection seismic phases from all the useful OBSs and land stations (Liu et al, 2015;Liu et al, 2021). We found that most of the OBS stations provided useful data at offsets of up to 100 km (Figure 5), although a few OBS stations only provided effective observations within 60 km offsets.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the phases in the Bohai Sea and SYS had the same distribution, but the refractions within the upper crust of the northern SYS had lower travel times and larger apparent velocities than those in the Bohai Sea from offset 0 km to about 120 km, indicating a roughly 120-km scale high-velocity anomaly in the upper crust of the northern SYS. The high-velocity anomaly was linked to the exhumation of the UHPM rocks in the SLOB (Liu et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations